Functional properties of navy bean (Phaseolus vulgaris) protein concentrates obtained by pneumatic tribo-electrostatic separation. (15th June 2019) - Tabtabaei, Solmaz; Konakbayeva, Dinara; Rajabzadeh, Amin Reza; Legge, Raymond L.
Highlights: Dry tribo-electrostatic separation can produce plant protein-rich fractions. Biochemical, microstructural and functional properties of fractions were analyzed. Protein-rich fractions showed superior solubility compared to wet process isolates. Protein-rich fractions also showed superior emulsifying and foaming properties. Dry tribo-electrostatic separation preserves native functionality of the proteins. Abstract: A sustainable, chemical-free dry tribo-electrostatic separation approach was employed to fractionate navy bean flour. The resulting protein-enriched fractions had 36–38% protein on a moisture free basis, accounting for 43% of the total available protein. SDS-PAGE analysis of the dry-enriched protein fractions showed a similar protein profile to that of the original navy bean flour. The functional properties of these fractions were examined and compared with the commercial soybean protein concentrate as well as navy bean protein isolate obtained by a conventional wet fractionation process. These electrostatically separated protein fractions exhibited superior solubility at their intrinsic pH as well as superior emulsion stability (ES), foam expansion (FE) and foam volume stability (FVS) compared to the wet-fractionated navy bean protein isolate that was almost depleted of albumins, exhibiting poor solubility and foaming properties. These results suggest electrostatic separation as a promising route to deliver functional protein concentrates as novel food formulation ingredients.